Traditional Therapy in Postpartum Care: A Qualitative Study in Neniari Village, Manggarai Regency, East Nusa Tenggara - Handayani, Teti Yuli (HM Publisher, 2024)
The postpartum period is an important period for mothers to recover their physical and psychological condition after giving birth. In Indonesia, there are various traditional practices carried out to care for postpartum mothers. This research aims to explore traditional therapeutic practices in postpartum care in Neniari Village, Manggarai Regency, East Nusa Tenggara. This research uses a qualitative study method with a phenomenological approach. Data was collected through in-depth interviews with 10 postpartum mothers and 3 traditional birth attendants. The research results show that there are three types of traditional therapy that are commonly practiced in Neniari Village, namely: Herbal concoctions: Herbal concoctions are used to treat various complaints experienced by postpartum mothers, such as bleeding, abdominal pain and breast swelling. Ukup: Ukup is a massage technique performed to improve blood circulation, reduce pain, and improve mood. Rahu: Rahu is a steaming technique performed to warm the body, tone the uterine muscles and increase breast milk production. The research results show that traditional therapy has many benefits for postpartum mothers, both physically and psychologically. Traditional therapy can also be an alternative postpartum care that is affordable and easy to obtain.